Public awareness of testicular cancer and testicular self-examination in academic environments: a lost opportunity (Clinics, 2011)
BACKGROUND: Although testicular cancer is the most common cancer among 18- to 50-year-old males, healthcare providers seldom teach testicular self-examination techniques to clients, thus potentially missing opportunities for early detection. This form of cancer is easily diagnosable by testicular self-examination and is 96% curable if detected early. Periodic self-examination must be performed for early detection. Knowledge deficits and sociocultural norms contribute to low levels of health-related knowledge in most patients, resulting in undue delays before seeking medical advice. OBJECTIVE: Our aim is to assess the level of awareness of testicular cancer and the prevalence of the practice of testicular self-examination in academic environments to enable appropriate interventions. METHOD: A cross-sectional survey was administered to 750 consecutive males aged 18-50 years in three tertiary institutions in Port Harcourt from October 2008 to April 2009. RESULT: Knowledge or awareness of testicular cancer was poor. Almost all of the respondents were unaware that testicular lumps may be signs of cancer. A lump was typically construed as a benign carbuncle or something that could resolve spontaneously. The main factor contributing to respondents' lack of knowledge of testicular cancer was that few reported that they were "ever taught about testicular self-examination." CONCLUSION: Young adult men are unaware of their risk for testicular cancer, which is the most common neoplasm in this age group. Healthcare providers are not informing them of this risk, nor are they teaching them the simple early detection technique of self-examination of the testes.